2013
DOI: 10.1016/j.aquatox.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid endocrine disruption in zebrafish larvae following exposure to hexaconazole and tebuconazole

Abstract: The widely used triazole fungicides have the potential to disrupt endocrine system, but little is known of such effects or underlying mechanisms of hexaconazole (HEX) and tebuconazole (TEB) in fish. In the present study, zebrafish (Danio rerio) embryos were exposed to various concentrations of HEX (0.625, 1.25 and 2.5 mg/L) and TEB (1, 2 and 4 mg/L) from fertilization to 120 h post-fertilization (hpf). The whole body content of thyroid hormone and transcription of genes in the hypothalamic-pituitary-thyroid (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
74
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(85 citation statements)
references
References 40 publications
10
74
1
Order By: Relevance
“…Thyroiddisrupting effects have been reported for, e.g. polychlorinated biphenyls, polyaromatic hydrocarbons, polybrominated diphenyl ethers, organochlorine pesticides as well as different metals (Brown et al, 2004;Yu et al, 2013). Those environmental chemicals appear to interfere with the thyroid system of vertebrates by two principal molecular mechanisms: a) Disrupting the thyroid hormone homeostasis, which includes effects on enzymes responsible for iodine uptake and thyroid hormone synthesis, and transport in the blood, on cellular uptake degradation and excretion = thyroid gland function disruptors (Thienpont et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thyroiddisrupting effects have been reported for, e.g. polychlorinated biphenyls, polyaromatic hydrocarbons, polybrominated diphenyl ethers, organochlorine pesticides as well as different metals (Brown et al, 2004;Yu et al, 2013). Those environmental chemicals appear to interfere with the thyroid system of vertebrates by two principal molecular mechanisms: a) Disrupting the thyroid hormone homeostasis, which includes effects on enzymes responsible for iodine uptake and thyroid hormone synthesis, and transport in the blood, on cellular uptake degradation and excretion = thyroid gland function disruptors (Thienpont et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an in vivo model for testing endocrine disruption of THs was developed using zebrafish larvae (Yu et al, 2010;Schmidt and Braunbeck, 2011). This assay indicated that the zebrafish HPT axis can be used to determine thyroid endocrine system disruption by TH endocrine disruptors, and also, to some extent, to indicate potential mechanisms of action, e.g., polybrominated diphenyl ethers (PBDEs) (Yu et al, 2010;Chan and Chan, 2012), herbicide ioxynil (Campinho and Power, 2013), fungicides hexaconazole and tebuconazole (Yu et al, 2013), and triclosan (Pinto et al, 2013). However, the disruption of the thyroid endocrine system by PCP and the environmental risk to fish remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A lower level of T 4 may be due to an increased activity of UDP-transferase which responsible for glucuronidation and clearance of T 4 (Zhou et al, 2001;Hallgren and Darnerud, 2002). Yu et al (2013) reported that a significant decrease in T 4 level in D. rerio exposed to the fungicides hexaconazole and tebuconazole indicate thyroid endocrine disruption. A significant decrease of T 4 levels was observed in zebrafish larvae with decabromodiphenyl ether (BDE-209) exposure whereas T 3 levels were significantly increased indicating that polybrominated diphenyl ethers (PBDE) induce thyroid endocrine disruption by disturbing T 4 levels, but the changes in T 3 levels may depend on exposure time, species or concentrations.…”
Section: Discussionmentioning
confidence: 98%